Human papillomavirus and associated factors in patients with unknown cytology treated in northern Peru - Iglesias-Osores, Sebastián (2020)
Background: Human papillomavirus is cause of cervical cancer, one of the most common cancers among women. Objective: To determine the prevalence of human papillomavirus and associated factors in patients with unknown cytology. Methods: In gynecology patients with unknown cytology attended at Lambayeque Regional Hospital, at the northern coast of Peru, from April through June 2019, DNA extraction for human papillomavirus identification performed on cervical samples was based on the salting out method. Samples were processed by polymerase chain reaction. All samples were amplified for MY09 and MY11 primers, and PC04 / GH20 primers. Bivariate analysis used the chi-square and t-student tests. Results: 29.9% of the patients studied were infected with human papillomavirus. No statistically significant difference was found between human papillomavirus infection and age, age at first sexual intercourse, promiscuity, number of vaginal deliveries, cervical lesion, history of sexually transmitted infections, use of hormonal contraceptive or condoms, and smoking.